2023
DOI: 10.1177/02698811231200023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy and safety of a novel standardized ashwagandha (Withania somnifera) root extract (Witholytin®) in adults experiencing high stress and fatigue in a randomized, double-blind, placebo-controlled trial

Stephen J Smith,
Adrian L Lopresti,
Timothy J Fairchild

Abstract: Background: Stress is a state of homeostasis in the body being challenged, resulting in a systemic response. It has become more prevalent in recent years and affects mental and physical health. Aims: Evaluate the effects of ashwagandha on stress, fatigue, and sex hormones in overweight or mildly obese men and women with self-reported stress and fatigue. Methods: Two-arm, parallel-group, 12-week, randomized, double-blind, placebo-controlled trial on overweight or mildly obese men and women aged 40–75 years, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…These findings are consistent with results from Chandrasekhar et al [ 6 ], who reported that ashwagandha supplementation (2 × 300 mg/d for 60 days) in individuals with a history of stress and anxiety had no clinically significant effects on clinical blood parameters or reported side effects. Additionally, results support findings from Smith and coworkers [ 18 ], who reported that 2 × 200 mg/d of ashwagandha root extract supplementation for 12 weeks in overweight men and women between the ages of 40–75 years experiencing high levels of fatigue and stress did not significantly affect blood glucose, HbA1c, cell blood counts, markers liver function, markers of renal function, or perceptions of side effects. Current findings also support other studies reporting that ashwagandha supplementation (500–700 mg/d for 2–8 weeks) in adults was well-tolerated and did not result in perceptions of side effects [ 33 , 64 , 70 , 71 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings are consistent with results from Chandrasekhar et al [ 6 ], who reported that ashwagandha supplementation (2 × 300 mg/d for 60 days) in individuals with a history of stress and anxiety had no clinically significant effects on clinical blood parameters or reported side effects. Additionally, results support findings from Smith and coworkers [ 18 ], who reported that 2 × 200 mg/d of ashwagandha root extract supplementation for 12 weeks in overweight men and women between the ages of 40–75 years experiencing high levels of fatigue and stress did not significantly affect blood glucose, HbA1c, cell blood counts, markers liver function, markers of renal function, or perceptions of side effects. Current findings also support other studies reporting that ashwagandha supplementation (500–700 mg/d for 2–8 weeks) in adults was well-tolerated and did not result in perceptions of side effects [ 33 , 64 , 70 , 71 ].…”
Section: Discussionsupporting
confidence: 88%
“…Ashwagandha has been reported to possess antioxidant [ 9 , 14 , 15 , 16 ], anti-inflammatory [ 9 , 11 , 12 ], neuroprotective [ 8 , 10 , 15 , 23 , 24 , 25 , 26 ], endocrinological [ 17 , 18 , 19 , 20 , 21 ], and immune-modulatory properties [ 10 , 22 ] that influence cognition [ 1 , 23 , 25 , 31 ]. Preliminary human clinical trials indicate that ashwagandha supplementation may have therapeutic benefits in individuals with medically managed bipolar disease [ 32 ], mild cognitive impairment [ 33 ], and chronic stress [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). 16 A randomized controlled trial demonstrated that Ashwagandha root extract supplementation significantly re- Antioxidant; Anti-inflammatory duced stress, anxiety, and depression symptoms in individuals with chronic stress, highlighting its potential as a natural stress-management remedy. 17 A recent review explored the potential of Ashwagandha for managing stress and anxiety.…”
Section: Ashwagandha (Withania Somnifera (L) Dunal)mentioning
confidence: 99%